Analisis Nilai-Nilai Toleransi Beragama Yang Terkandung Dalam Surah Al Kafirun: Membangun Pondasi Pendidikan Multikultural: Analysis of the Values of Religious Tolerance Contained in Surah Al-Kafirun: Building the Foundation of Multicultural Education - Mubarakatun Nikmah; Yogi Sopian Haris (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
Multicultural education in Indonesia requires an approach that can integrate values of tolerance and respect for religious and cultural differences.  One of the primary sources for building a strong foundation for multicultural education is the teachings in the Qur'an, especially Surah Al-Kafirun.  This research aims to analyze the values of religious tolerance contained in Surah Al-Kafirun and its relevance in building multicultural education.  The method used in this research is a library method with a content analysis approach.  This research examines the text of Surah Al-Kafirun in depth to identify values that can be applied in multicultural education, such as appreciation for differences, mutual respect, and recognition of religious freedom.  The research results show that Surah Al-Kafirun teaches the basic principles of religious tolerance, including respect for others' religious choices, acknowledging differences as part of God's will, and maintaining harmonious relationships despite differing beliefs.  In the context of multicultural education, this surah teaches values of respect for differences, an inclusive attitude, and the ability to resolve conflicts peacefully.  This surah-based learning model, such as the dialogic approach and collaborative projects, helps students understand diversity and strengthen interfaith cooperation.  In addition, this surah supports the strengthening of Indonesia's national identity by teaching the importance of unity in diversity.